Biorafinerijski potencial manjvrednega lesa rdečega bora (Pinus sylvestris L.) in robinije (Robinia pseudoacacia L.) za pridobivanje naravnih bioaktivnih učinkovin za zaščito lesa - Vek, Viljem (Acta silvae et ligni, 2025)
This article presents the key results and scientific findings from two national postdoctoral research projects supported by the Ministry of Education, Science and Sport of the Republic of Slovenia (MIZŠ) and the Slovenian Research and Innovation Agency (ARIS). We analyzed the biorefinery potential of low-value Scots pine (Pinus sylvestris L.) and black locust (Robinia pseudoacacia L.) wood for the extraction of natural bioactive compounds. Knotwood and heartwood were used as biomass for extracting polyphenolic compounds, which were subsequently applied in bio-based wood preservatives. The results showed that hydrophilic extractives from Scots pine knotwood and black locust heartwood inhibit fungal decay and demonstrate strong potential as biocidal components and antioxidants in natural wood protection formulations. Further research on the antioxidant and antifungal properties of wood and bark extractives is ongoing.
Keywords: biorafinerija; biorefinery; black locust; circular bioeconomy; ekstrakcija; extraction; grče; knotwood; krožno biogospodarstvo; les; low-value tree biomass; manjvredna drevesna biomasa; naravni fungicidi in antioksidanti; natural fungicides and antioxidants; polifenoli; polyphenols; rdeči bor; robinija; Scots pine; wood